Intimate Partner Violence Against Pregnant Jordanian Women at the Time of COVID-19 Pandemic’s Quarantine - Abujilban, Sanaa (Journal of interpersonal violence, 2022)
In Jordan, women experience considerable levels of different types of violence. The emerging data from different countries indicate that intimate partner violence (IPV) has intensified since the COVID-19 outbreak. The main purpose of the current study is to find out whether there is any difference in the incidence of IPV during and before the COVID-19 pandemic quarantine and whether any sociodemographical factors are related to the incidence of IPV against pregnant women during quarantine. A cross-sectional, correlational design was in this study. The snowball sampling technique was adopted to select the participants, which produced a nonrepresentative sample of 215 pregnant women. The participants completed the Arabic version of the World Health Organization?s Domestic Violence Questionnaire Screening Tool (DVQST). We found that women were exposed to different types of IPV before and during the quarantine. The most prevalent form of IPV was control and humiliation (n 172, 80%) and the least prevalent was sexual violence ((n 33, 15.3%), (n 24, 11.2%), respectively). However, there were statistically significant lower DVQST scores during the COVID-19 quarantine than before the quarantine. All types of IPV are significantly correlated with each other and with relationship problems (marital conflict, verbal fighting, understanding each other). While the findings are not generalizable to the general population of pregnant women in Jordan because the sample consisted only of women of high socioeconomic status due to the use of a nonprobability sampling technique, national campaigns should be developed and implemented in order to reduce IPV and change community behaviors and attitudes toward violence against women. It is also recommended that policymakers develop plans to help pregnant women during quarantine by, for example, training care providers on how to access vulnerable women.